A repairable and recyclable fiber-reinforced resin-based composite material with damage reporting and a preparation method thereof
By using non-stoichiometric covalent crosslinked epoxy resin and curing agent in fiber-reinforced resin-based composite materials, combined with dynamic transesterification reaction and microcapsule technology, the self-healing of composite materials, self-reporting of damage and fiber recovery is achieved, and the problem of difficulty in repairing and recycling of existing composite materials is solved.
Patent Information
- Application Number
- CN202310379723.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-04-11
AI Technical Summary
Existing fiber-reinforced thermosetting resin-based composites are difficult to self-report damage, repair and recycling, and the damage analysis process is time-consuming and the equipment is complex.
The epoxy resin monomer and curing agent are covalently cross-linked by non-stoichiometric method, and multiple hydrogen bonds are formed through dual cross-linking, which gives the composite material self-healing ability and realizes the recovery function through dynamic transesterification reaction. The microcapsule release core material undergoes proton exchange with the amine group, resulting in a bright yellow color at the damaged position, realizing self-report of damage.
The composite material has been repaired multiple times at room temperature to meet the performance requirements of continuing to serve, and self-reporting damage and fiber recovery under the action of external forces, avoiding the complex and time-consuming problem of the damage repair process of traditional composite materials.
Smart Images

Figure CN116199915B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical fields of composite material preparation, structural damage monitoring, degradation and composite material fiber recycling, and in particular to a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting and a preparation method thereof. Background Art
[0002] Fiber-reinforced thermosetting resin-based composites (FRCs) are widely used in aerospace fields such as aircraft structures, satellite and space station components, aircraft and rocket protective covers due to their excellent mechanical properties and light weight. They are still expanding into new application areas and are in a period of rapid expansion. Although FRCs have excellent mechanical properties, crack damage on the surface of composite materials will affect the integrity and functionality of the material even at a small scale, and this damage is often invisible. At present, the damage analysis process such as industrial pulse thermal imaging and X / γ-ray methods is time-consuming and complex. In order to accurately determine the location and degree of material failure, the development of an efficient polymer material with a damage self-reporting monitoring structure is of great strategic significance for expanding the application of FRCs.
[0003] At the same time, due to the permanent cross-linked network structure of its resin matrix, the existing FRCs damage (delamination and cracks, etc.) repair process is complex and time-consuming. Most importantly, the recycling and reuse of carbon fibers is very difficult. Currently, the commonly used composite fiber recycling methods mainly include mechanical recycling, chemical recycling and thermal decomposition. The mechanical recycling method is to mechanically cut the composite material and use it as a reinforcing filler. This method changes the aspect ratio of the fiber. From a long-term perspective, the mechanical recycling method cannot obtain the most valuable carbon fiber in the composite material, so this method is a low-value recovery. The chemical recovery method often requires the use of highly corrosive solvents (such as concentrated nitric acid, etc.), and the thermal decomposition method requires harsh high temperature and high pressure conditions to decompose the resin matrix, which is not conducive to industrial application.
[0004] Chinese invention patent CN202110716549.0 discloses an epoxy resin composite material with dual functions of damage self-reporting. Due to its high glass transition temperature and network rigidity, the composite material can only report damage but not repair it. Moreover, this function of reporting damage by free radicals can only last for a few hours, and its function needs to be further optimized.
[0005] In view of the above, it is necessary to develop repairable and recyclable carbon fiber composites with damage reporting, which can achieve the repair of composite materials and fiber recycling under mild conditions while ensuring the mechanical properties of the materials. Summary of the invention
[0006] In aviation / aerospace vehicles, the proportion of FRCs materials has become an important indicator to measure whether the performance of the aircraft is excellent. Furthermore, efficient and high-performance FRCs component damage repair, recycling and self-reporting of damage have become research hotspots in the current field of composite material applications. The present invention provides a method for preparing a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, which solves the problems of the above-mentioned fiber-reinforced resin-based composite material being difficult to self-report damage, difficult to repair, difficult to degrade, and damaged performance and structure of the fiber reinforcement after recycling.
[0007] The present invention adopts a non-stoichiometric covalent cross-linking method for epoxy resin monomers and curing agents. On the one hand, the hydroxyl groups generated by the epoxy ring opening form multiple hydrogen bonds with the primary amines provided by the curing agent. Due to the double cross-linking effect, the resulting composite material not only has good mechanical strength, but also gives the resin matrix self-healing ability at room temperature. On the other hand, the tertiary amine provided by the curing agent can trigger a dynamic transesterification reaction inside the resin at high temperature, thereby realizing the recycling function of the composite material. Ingeniously, the core material released from the damaged microcapsule also undergoes proton exchange with the amine group, resulting in a bright yellow color at the damaged position, and then self-reporting damage in the damaged area, and this color change has good stability.
[0008] The specific technical solutions of the present invention are as follows:
[0009] In a first aspect, the present invention provides a method for preparing a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, comprising the following steps:
[0010] The epoxy resin and the curing agent are uniformly mixed to obtain a pre-gelatin solution; the curing agent has at least one amine group in its structure;
[0011] adding microcapsules into the pregel solution to obtain a mixed pregel solution;
[0012] The mixed pre-glue liquid is injected into the fiber preform, and the mixture is cured and cross-linked to obtain a fiber-reinforced resin-based composite material.
[0013] Furthermore, the epoxy resin is at least one epoxy resin to ensure its cross-linking density, and the epoxy resin has at least two epoxy functional groups.
[0014] Furthermore, the epoxy resin is one of glycidyl ester epoxy resin, glycidyl ether epoxy resin, ester ring epoxy resin or a mixture of several thereof.
[0015] Furthermore, the curing agent is one or a mixture of polyethyleneimine, aniline, 2,2'-diaminodiphenylmethane, and 2,2'-diaminodiphenyl ether.
[0016] Furthermore, the fibers in the fiber-reinforced resin-based composite material are long fiber reinforcements, and the mass fraction of the long fiber reinforcements accounts for 65-70% of the total content of the epoxy resin, the curing agent, and the fibers.
[0017] Furthermore, the molar ratio of the epoxy resin to the curing agent is 0.7-2.
[0018] Furthermore, the mass fraction of the microcapsules accounts for 1-5% of the total content of the epoxy resin and the curing agent.
[0019] Furthermore, at room temperature, the epoxy resin and the curing agent are uniformly mixed to obtain the pre-glue solution.
[0020] Furthermore, the preparation steps of the microcapsules include:
[0021] Deionized water, urea and formaldehyde are mixed uniformly, the pH is adjusted to alkaline with triethylamine, and the mixture is kept at 50 to 60° C. for 2 to 3 hours under magnetic stirring to obtain a prepolymer solution;
[0022] Slowly drop an anionic emulsifier sodium dodecyl sulfate aqueous solution or sodium dodecylbenzene sulfonate aqueous solution into the prepared prepolymer solution for emulsification, then add 2,7-dichlorofluorescein, stir for 20 to 30 minutes, slowly adjust the pH of the emulsion to 3 to 4 with phosphoric acid or sulfuric acid, react for 2 to 4 hours, and obtain a microcapsule suspension;
[0023] The obtained microcapsule suspension is cooled to room temperature, rinsed with deionized water and acetone, and dried to obtain microcapsules of a certain size range. This method forms single-shell microcapsules, the shell layer of the microcapsules is a polyurea polymer, and the core material inside the microcapsules is 2,7-dichlorofluorescein.
[0024] Further, laying the fibers in a metal mold to obtain the fiber preform;
[0025] Furthermore, the method of injecting the mixed prepared glue solution into the fiber preform, curing and cross-linking, and obtaining a fiber-reinforced resin-based composite material comprises: injecting the mixed prepared glue solution b into the fiber preform under a pressure of 0.1 to 0.5 MPa through an RTM process, curing and cross-linking, and obtaining a fiber-reinforced resin-based composite material.
[0026] Furthermore, the emulsification conditions are: treating at 60-65° C. for 2-3 hours.
[0027] Furthermore, before the mixed pre-glue solution is injected into the fiber preform, it is first placed in a vacuum oven at 40 to 50° C. for 20 to 30 minutes to remove gas from the resin solution.
[0028] Furthermore, the curing conditions are: treating at 70-120° C. for 2-3 h, treating at 120-160° C. for 3-6 h, and treating at 160-190° C. for 2-3 h.
[0029] Furthermore, the long fiber reinforcement includes: carbon fiber, glass fiber, plant fiber or aramid fiber.
[0030] In a second aspect, the present invention provides a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting prepared by the above method.
[0031] Furthermore, when the fiber-reinforced resin-based composite material is impacted by external force, the core material released from the damaged microcapsules undergoes proton exchange with the amine groups in the resin, causing the damaged area to appear bright yellow, showing mechanochromism, and then self-reporting damage at the damaged location.
[0032] Furthermore, after the fiber-reinforced resin-based composite material is damaged, pressure is applied to the composite material, and the damage can be healed after a certain period of time. For example, a pressure of 10 MPa is applied to the composite material at room temperature, and the damage can be healed after 72 hours.
[0033] Furthermore, the fiber-reinforced resin-based composite material is degraded in a degradation liquid containing hydroxyl groups at a temperature of 140 to 160°C.
[0034] Furthermore, the degradation liquid includes: one or a mixture of water, methanol, ethylene glycol, and glycerol.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) A repairable and recyclable fiber-reinforced resin-based composite material with damage reporting prepared by the present invention has good mechanical strength due to the double cross-linking effect, and the tensile strength of the matrix material is 60-75MPa. The prepared repairable and recyclable fiber-reinforced resin-based composite material with damage reporting has a tensile strength of ≥400MPa. At the same time, the hydroxyl groups generated by epoxy ring opening form multiple network hydrogen bonds with primary amines, so that the resin material and the composite material can repair cracks, gaps and other difficult-to-detect damages at room temperature many times, meet the performance requirements for continued service, and solve the problem of the contradiction between high mechanical properties and healing properties.
[0037] (2) When the material is impacted by external force, the core material released from the damaged microcapsules undergoes proton exchange with the amine groups in the resin, causing the damaged area to appear bright yellow, showing mechanochromism, and then self-reporting damage at the damaged location. This color change has good stability.
[0038] (3) The present invention realizes mild degradation of fiber-reinforced resin-based composite materials based on internal tertiary amine catalysis. The degradation of general epoxy resins requires the addition of catalysts or other strong bases, strong acids, etc., but the present invention can undergo network re-esterification (ester exchange) without any catalyst, thereby achieving complete degradation of fiber-reinforced epoxy resin-based composite materials while ensuring mechanical properties comparable to those of traditional epoxy resin-based composite materials, and the recovered fiber reinforcement is consistent with the original fiber performance structure.
[0039] Combining the above advantages, this polymer composite material can not only heal and recycle, but also monitor material damage, and has potential application prospects in aerospace, information encryption and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 . Schematic diagram of the healing and damage reporting mechanism of the fiber-reinforced resin-based composite material in the present invention.
[0041] Figure 2 .SEM images of the fiber-reinforced resin-based composite material of the present invention during and after degradation.
[0042] Figure 3 .The stress-strain curve of the fiber-reinforced resin-based composite material before and after healing in the present invention, wherein the abscissa represents the tensile strain and the ordinate represents the tensile stress. DETAILED DESCRIPTION
[0043] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with the embodiments, which are only used to explain the present invention and do not limit the protection scope of the present invention. All variations that can be associated or derived are considered to be within the protection scope of the present invention.
[0044] In the following embodiments of the present invention, the tensile properties of the materials are tested according to ISO1268-1-2001 standard; in the material degradation experiment test, parallel specimens of the materials are placed in 140-150°C ethylene glycol degradation solution, and points are taken at intervals of 20-30 minutes by weighing method, and the microscopic changes in the degradation process are analyzed by scanning electron microscopy (SEM).
[0045] Example 1
[0046] In this embodiment, 4,5-epoxyhexane-1,2-dicarboxylic acid diglycidyl ester and polyethyleneimine were purchased from Shanghai Anaiji Chemical Co., Ltd. Formaldehyde, 2,7-dichlorofluorescein, urea, triethylamine, sodium dodecyl sulfate, and phosphoric acid were purchased from San Chemical Technology (Shanghai) Co., Ltd. Glass fiber fabric (EW250F) was purchased from Nanjing Glass Fiber Research and Design Institute.
[0047] This embodiment includes a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, comprising the following steps:
[0048] Step M-1: at room temperature, uniformly mix 4,5-epoxyhexane-1,2-dicarboxylic acid diglycidyl ester and polyethyleneimine to obtain a pregel solution a;
[0049] Step M-2: deionized water, urea and formaldehyde are mixed uniformly, the pH is adjusted to alkaline with triethylamine, and the mixture is kept at 55° C. for 2 hours under magnetic stirring to obtain a prepolymer solution; then, an emulsifier sodium dodecyl sulfate aqueous solution is slowly added dropwise to the prepolymer solution prepared above for emulsification, and then 2,7-dichlorofluorescein is added; after stirring for 20 minutes, the pH of the emulsion is slowly adjusted to 3 to 4 with phosphoric acid; after 3 hours, the obtained microcapsule suspension is cooled to ambient temperature, filtered, washed and dried to obtain microcapsules in the range of 55 to 70 μm;
[0050] Step M-3: adding the microcapsules prepared in step M-2 to the pregel solution a in step M-1 to obtain a mixed pregel solution b;
[0051] Step M-4: Laying the fiber in a metal mold to obtain a fiber preform;
[0052] Step M-5: Through the RTM process, at a pressure of 0.1 MPa, the mixed preparatory adhesive solution b prepared in M3 is injected into the fiber preform of step M-4, and cured and cross-linked to obtain a fiber-reinforced epoxy resin-based composite material.
[0053] Step M-6: Degrading the material prepared in this example, degradation step: placing the sample in ethylene glycol solution, weighing the remaining mass of the sample every 30 minutes at 160° C. Taking out the separated glass fiber bundle, the surface of the recycled fiber is clean and undamaged.
[0054] in:
[0055] The emulsification conditions were: treatment at 60°C for 2 h;
[0056] Before the mixed pre-glue solution b is injected into the fiber preform, it is first placed in a vacuum oven at 45°C for 20 minutes to remove gas from the resin solution;
[0057] The curing conditions are: 2 h at 90 °C, 5 h at 120 °C, and 3 h at 160 °C.
[0058] Figure 1The figure is a schematic diagram of the healing and damage reporting mechanism of fiber-reinforced resin-based composites. The solid line is a covalent bond, the dotted line is a hydrogen bond, and the dark gray sphere is a microcapsule. When the material is impacted by an external force, the core material released from the damaged microcapsule undergoes a proton exchange with the amine group in the resin, resulting in a bright yellow color visible to the naked eye in the damaged area, showing mechanochromism, and then self-reporting the damage at the damaged location. When a pressure of 10MPa is applied to the composite material at room temperature, the damage can be healed after 72 hours. The performance data of the composite material are shown in Tables 1 and Figure 3 The fiber bundles during the degradation process and after degradation recovery were analyzed by scanning electron microscopy (SEM), as shown in Figure 2 As shown, the surface of the recycled glass fiber is clean and undamaged.
[0059] Example 2
[0060] In this embodiment, diglycidyl tetrahydrophthalate and polyethyleneimine were purchased from Shanghai Anaiji Chemical Co., Ltd. Formaldehyde, 2,7-dichlorofluorescein, urea, triethylamine, sodium dodecyl sulfate, and phosphoric acid were purchased from San Chemical Technology (Shanghai) Co., Ltd. T800 carbon fiber fabric (CCF800S) was purchased from Weihai Guangwei Composite Materials Co., Ltd., China.
[0061] This embodiment includes a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, comprising the following steps:
[0062] Step M-1: at 40° C., diglycidyl tetrahydrophthalate and polyethyleneimine are uniformly mixed to obtain a pregel solution a;
[0063] Step M-2: deionized water, urea and formaldehyde are mixed uniformly, the pH is adjusted to alkaline with triethylamine, and the mixture is kept at 55° C. for 2 hours under magnetic stirring to obtain a prepolymer solution; then, an emulsifier sodium dodecyl sulfate aqueous solution is slowly added dropwise to the prepolymer solution prepared above for emulsification, and then 2,7-dichlorofluorescein is added; after stirring for 20 minutes, the pH of the emulsion is slowly adjusted to 3 to 4 with phosphoric acid; after 3 hours, the obtained microcapsule suspension is cooled to ambient temperature, filtered, washed and dried to obtain microcapsules in the range of 55 to 70 μm;
[0064] Step M-3: adding the microcapsules prepared in step M-2 to the pregel solution a in step M-1 to obtain a mixed pregel solution b;
[0065] Step M-4: Laying the fiber in a metal mold to obtain a fiber preform;
[0066] Step M-5: Through the RTM process, at a pressure of 0.15 MPa, the mixed pre-glue solution b prepared in M3 is injected into the fiber preform of step M-4, and cured and cross-linked to obtain a fiber-reinforced epoxy resin-based composite material.
[0067] Step M-6: Degrading the material prepared in this example, degradation step: placing the sample in an ethylene glycol solution, weighing the remaining mass of the sample every 30 minutes at 160° C. Taking out the separated carbon fiber bundles, the surface of the recycled fiber is clean and undamaged.
[0068] in:
[0069] The emulsification conditions were: treatment at 60°C for 3 h;
[0070] Before the mixed pre-glue solution b is injected into the fiber preform, it is first placed in a vacuum oven at 40°C for 30 minutes to remove gas from the resin solution;
[0071] The curing conditions are: 70°C for 3 hours, 160°C for 3 hours, and 190°C for 2 hours.
[0072] The performance data of the composite material prepared in this example are shown in Table 1.
[0073] Example 3
[0074] In this embodiment, trimesic acid triglycidyl ester and aniline were purchased from Shanghai Anaiji Chemical Co., Ltd. Formaldehyde, 2,7-dichlorofluorescein, urea, triethylamine, sodium dodecyl sulfate, and phosphoric acid were purchased from San Chemical Technology (Shanghai) Co., Ltd. Glass fiber fabric (EW250F) was purchased from Nanjing Glass Fiber Research and Design Institute.
[0075] This embodiment includes a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, comprising the following steps:
[0076] Step M-1: at 85° C., uniformly mix triglycidyl trimesic acid and aniline to obtain a pregel solution a;
[0077] Step M-2: deionized water, urea and formaldehyde are mixed uniformly, the pH is adjusted to alkaline with triethylamine, and the mixture is kept at 55° C. for 2 hours under magnetic stirring to obtain a prepolymer solution; then, an emulsifier sodium dodecyl sulfate aqueous solution is slowly added dropwise to the prepolymer solution prepared above for emulsification, and then 2,7-dichlorofluorescein is added; after stirring for 20 minutes, the pH of the emulsion is slowly adjusted to 3 to 4 with phosphoric acid; after 3 hours, the obtained microcapsule suspension is cooled to ambient temperature, filtered, washed and dried to obtain microcapsules in the range of 55 to 70 μm;
[0078] Step M-3: adding the microcapsules prepared in step M-2 to the pregel solution a in step M-1 to obtain a mixed pregel solution b;
[0079] Step M-4: Laying the fiber in a metal mold to obtain a fiber preform;
[0080] Step M-5: Through the RTM process, at a pressure of 0.5 MPa, the mixed pre-glue solution b prepared in M3 is injected into the fiber preform of step M-4, and cured and cross-linked to obtain a fiber-reinforced epoxy resin-based composite material.
[0081] Step M-6: Degrading the material prepared in this example, degradation step: placing the sample in ethylene glycol solution, weighing the remaining mass of the sample every 30 minutes at 160° C. Taking out the separated glass fiber bundle, the surface of the recycled fiber is clean and undamaged.
[0082] in:
[0083] The emulsification conditions were: treatment at 65°C for 2 h;
[0084] Before the mixed pre-glue solution b is injected into the fiber preform, it is first placed in a vacuum oven at 45°C for 30 minutes to remove gas from the resin solution;
[0085] The curing conditions are: 3 h at 100 °C, 5 h at 160 °C, and 2 h at 160 °C.
[0086] The performance data of the composite material prepared in this example are shown in Table 1.
[0087] Example 4
[0088] In this embodiment, diglycidyl tetrahydrophthalate and 4,4-diaminodiphenylmethane were purchased from Shanghai Anaiji Chemical Co., Ltd. Formaldehyde, 2,7-dichlorofluorescein, urea, triethylamine, sodium dodecyl sulfate, and phosphoric acid were purchased from San Chemical Technology (Shanghai) Co., Ltd. T800 carbon fiber fabric (CCF800S) was purchased from Weihai Guangwei Composite Materials Co., Ltd.
[0089] This embodiment includes a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, comprising the following steps:
[0090] Step M-1: at 40° C., diglycidyl tetrahydrophthalate and 4,4-diaminodiphenylmethane are uniformly mixed to obtain a pregel solution a;
[0091] Step M-2: deionized water, urea and formaldehyde are mixed uniformly, the pH is adjusted to alkaline with triethylamine, and the mixture is kept at 55° C. for 2 hours under magnetic stirring to obtain a prepolymer solution; then, an emulsifier sodium dodecyl sulfate aqueous solution is slowly added dropwise to the prepolymer solution prepared above for emulsification, and then 2,7-dichlorofluorescein is added; after stirring for 20 minutes, the pH of the emulsion is slowly adjusted to 3 to 4 with phosphoric acid; after 3 hours, the obtained microcapsule suspension is cooled to ambient temperature, filtered, washed and dried to obtain microcapsules in the range of 55 to 70 μm;
[0092] Step M-3: adding the microcapsules prepared in step M-2 to the pregel solution a in step M-1 to obtain a mixed pregel solution b;
[0093] Step M-4: Laying the fiber in a metal mold to obtain a fiber preform;
[0094] Step M-5: Through the RTM process, at a pressure of 0.2 MPa, the mixed pre-glue solution b prepared in M3 is injected into the fiber preform of step M-4, and cured and cross-linked to obtain a fiber-reinforced epoxy resin-based composite material.
[0095] Step M-6: Degrading the material prepared in this example, degradation step: placing the sample in an ethylene glycol solution, weighing the remaining mass of the sample every 30 minutes at 160° C. Taking out the separated carbon fiber bundles, the surface of the recycled fiber is clean and undamaged.
[0096] in:
[0097] The emulsification conditions were: treatment at 60°C for 3 h;
[0098] Before the mixed pre-glue solution b is injected into the fiber preform, it is first placed in a vacuum oven at 50°C for 20 minutes to remove gas from the resin solution;
[0099] The curing conditions are: 120°C for 2 hours, 150°C for 6 hours, and 180°C for 3 hours.
[0100] The performance data of the composite material prepared in this example are shown in Table 1.
[0101] Example 5
[0102] In this embodiment, 4,5-epoxyhexane-1,2-dicarboxylic acid diglycidyl ester and polyethyleneimine were purchased from Shanghai Anaiji Chemical Co., Ltd. Formaldehyde, 2,7-dichlorofluorescein, urea, triethylamine, sodium dodecylbenzenesulfonate, and sulfuric acid were purchased from San Chemical Technology (Shanghai) Co., Ltd. Glass fiber fabric (EW250F) was purchased from Nanjing Glass Fiber Research and Design Institute.
[0103] This embodiment includes a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, comprising the following steps:
[0104] Step M-1: at room temperature, uniformly mix 4,5-epoxyhexane-1,2-dicarboxylic acid diglycidyl ester and polyethyleneimine to obtain a pregel solution a;
[0105] Step M-2: deionized water, urea and formaldehyde are mixed uniformly, the pH is adjusted to alkaline with triethylamine, and the mixture is kept at 55° C. for 2 hours under magnetic stirring to obtain a prepolymer solution; then, an aqueous solution of sodium dodecylbenzenesulfonate, an emulsifier, is slowly added dropwise to the prepolymer solution prepared above for emulsification, and then 2,7-dichlorofluorescein is added; after stirring for 20 minutes, the pH of the emulsion is slowly adjusted to 3 to 4 with sulfuric acid; after 3 hours, the obtained microcapsule suspension is cooled to ambient temperature, filtered, washed and dried to obtain microcapsules in the range of 55 to 70 μm;
[0106] Step M-3: adding the microcapsules prepared in step M-2 to the pregel solution a in step M-1 to obtain a mixed pregel solution b;
[0107] Step M-4: Laying the fiber in a metal mold to obtain a fiber preform;
[0108] Step M-5: Through the RTM process, at a pressure of 0.1 MPa, the mixed preparatory adhesive solution b prepared in M3 is injected into the fiber preform of step M-4, and cured and cross-linked to obtain a fiber-reinforced epoxy resin-based composite material.
[0109] Step M-6: Degrading the material prepared in this example, degradation step: placing the sample in ethylene glycol solution, weighing the remaining mass of the sample every 30 minutes at 160° C. Taking out the separated glass fiber bundle, the surface of the recycled fiber is clean and undamaged.
[0110] in:
[0111] The emulsification conditions were: treatment at 60°C for 2 h;
[0112] Before the mixed pre-glue solution b is injected into the fiber preform, it is first placed in a vacuum oven at 45°C for 20 minutes to remove gas from the resin solution;
[0113] The curing conditions are: 2 h at 90 °C, 5 h at 120 °C, and 3 h at 160 °C.
[0114] The performance data of the composite material prepared in this example are shown in Table 1.
[0115] Example 6
[0116] In this embodiment, diglycidyl tetrahydrophthalate and polyethyleneimine were purchased from Shanghai Anaiji Chemical Co., Ltd. Formaldehyde, 2,7-dichlorofluorescein, urea, triethylamine, sodium dodecylbenzenesulfonate, and sulfuric acid were purchased from San Chemical Technology (Shanghai) Co., Ltd. T800 carbon fiber fabric (CCF800S) was purchased from Weihai Guangwei Composite Materials Co., Ltd.
[0117] This embodiment includes a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, comprising the following steps:
[0118] Step M-1: at 40° C., diglycidyl tetrahydrophthalate and polyethyleneimine are uniformly mixed to obtain a pregel solution a;
[0119] Step M-2: deionized water, urea and formaldehyde are mixed uniformly, the pH is adjusted to alkaline with triethylamine, and the mixture is kept at 55° C. for 2 hours under magnetic stirring to obtain a prepolymer solution; then, an aqueous solution of sodium dodecylbenzenesulfonate, an emulsifier, is slowly added dropwise to the prepolymer solution prepared above for emulsification, and then 2,7-dichlorofluorescein is added; after stirring for 20 minutes, the pH of the emulsion is slowly adjusted to 3 to 4 with sulfuric acid; after 3 hours, the obtained microcapsule suspension is cooled to ambient temperature, filtered, washed and dried to obtain microcapsules in the range of 55 to 70 μm;
[0120] Step M-3: adding the microcapsules prepared in step M-2 to the pregel solution a in step M-1 to obtain a mixed pregel solution b;
[0121] Step M-4: Laying the fiber in a metal mold to obtain a fiber preform;
[0122] Step M-5: Through the RTM process, at a pressure of 0.15 MPa, the mixed pre-glue solution b prepared in M3 is injected into the fiber preform of step M-4, and cured and cross-linked to obtain a fiber-reinforced epoxy resin-based composite material.
[0123] Step M-6: Degrading the material prepared in this example, degradation step: placing the sample in an ethylene glycol solution, weighing the remaining mass of the sample every 30 minutes at 160° C. Taking out the separated carbon fiber bundles, the surface of the recycled fiber is clean and undamaged.
[0124] in:
[0125] The emulsification conditions were: treatment at 60°C for 3 h;
[0126] Before the mixed pre-glue solution b is injected into the fiber preform, it is first placed in a vacuum oven at 40°C for 30 minutes to remove gas from the resin solution;
[0127] The curing conditions are: 70°C for 3 hours, 160°C for 3 hours, and 190°C for 2 hours.
[0128] The performance data of the composite material prepared in this example are shown in Table 1.
[0129] Comparative Example 1
[0130] In this embodiment, triglycidyl triisocyanate and aniline were purchased from Shanghai Anaiji Chemical Co., Ltd. Formaldehyde, 2,7-dichlorofluorescein, urea, triethylamine, sodium dodecyl sulfate, and phosphoric acid were purchased from En Chemical Technology (Shanghai) Co., Ltd. Glass fiber fabric (EW250F) was purchased from Nanjing Glass Fiber Research and Design Institute.
[0131] step:
[0132] Step M-1: at 90° C., uniformly mix triglycidyl triisocyanate and aniline to obtain a pregel solution a;
[0133] Step M-2: deionized water, urea and formaldehyde are mixed uniformly, the pH is adjusted to alkaline with triethylamine, and the mixture is kept at 50-60°C for 2 hours under magnetic stirring; then, an aqueous solution of sodium dodecyl sulfate, an emulsifier, is slowly added dropwise to the prepolymer solution prepared above, and then 2,7-dichlorofluorescein is added; after stirring for 20 minutes, the pH of the emulsion is slowly adjusted to 3-4 with phosphoric acid; after 3 hours, the obtained microcapsule suspension is cooled to ambient temperature, filtered, washed and dried to obtain microcapsules in the range of 55-70 μm;
[0134] Step M-3: adding the microcapsules prepared in step M-2 to the pregel solution a in step M-1 to obtain a mixed pregel solution b;
[0135] Step M-4: Laying the fiber in a metal mold to obtain a fiber preform;
[0136] Step M-5: Through the RTM process, at a pressure of 0.5 MPa, the mixed pre-glue solution b prepared in M3 is injected into the fiber preform of step M-4, and cured and cross-linked to obtain a fiber-reinforced epoxy resin-based composite material.
[0137] Step M-6: The strips prepared in this example were placed in an ethylene glycol solution and were found to be not degraded at 160°C.
[0138] in:
[0139] The emulsification conditions are: 2h at 60℃;
[0140] Before the mixed pre-glue solution b is injected into the fiber preform, it is first placed in a vacuum oven at 90°C for 30 minutes to remove gas from the resin solution;
[0141] The curing conditions are: 100°C for 2h, 160°C for 4h, and 180°C for 3h.
[0142] Comparative Example 2
[0143] In this embodiment, triglycidyl triisocyanate and aniline were purchased from Shanghai Anaiji Chemical Co., Ltd. Glass fiber fabric (EW250F) was purchased from Nanjing Glass Fiber Research and Design Institute.
[0144] step:
[0145] Step M-1: at 90° C., uniformly mix triglycidyl triisocyanate and aniline to obtain a pregel solution a;
[0146] Step M-2: Laying the fiber in a metal mold to obtain a fiber preform;
[0147] Step M-3: Through the RTM process, at a pressure of 0.5 MPa, the mixed preparatory adhesive solution a prepared in M1 is injected into the fiber preform of step M-3, and cured and cross-linked to obtain a fiber-reinforced epoxy resin-based composite material.
[0148] in:
[0149] Before the mixed pre-glue solution a is injected into the fiber preform, it is first placed in a vacuum oven at 90°C for 30 minutes to remove gas from the resin solution;
[0150] The curing conditions are: 4 h at 120 °C, 6 h at 160 °C, and 3 h at 190 °C.
[0151] The performance data of Examples 1 to 6 and Comparative Examples 1 and 2 are shown in Table 1. As shown in Table 1, the reason why Examples 3 and 4 and Comparative Examples 1 and 2 cannot be damaged and repaired is due to the compactness of the network segments and the lack of sufficient network hydrogen bonds; the dynamic transesterification reaction cannot occur inside the resin of Comparative Examples 1 and 2 at high temperatures, so the material cannot be degraded and recycled; Comparative Example 2 has no microcapsules and therefore cannot be damaged and reported.
[0152] Table 1
[0153] Is the damage repairable? Is it degradable? Degradation time (h) Is it possible to report an injury? Example 1 yes yes 7 yes Example 2 yes yes 3 yes Example 3 no yes 11 yes Example 4 no yes 19 yes Example 5 yes yes 7 yes Example 6 yes yes 3 yes Comparative Example 1 no no - yes Comparative Example 2 no no - no
[0154] In summary, the present invention prepares a repairable and recyclable carbon fiber reinforced epoxy resin-based composite material with damage reporting, which solves the problems of difficult self-reporting damage, difficult repair and difficult recycling of traditional fiber reinforced epoxy resin-based composite materials. The present invention selects existing commercially available industrial raw materials, and on the basis of ensuring that the basic mechanical properties are comparable to those of traditional commercial fiber reinforced epoxy resin-based composite materials, the composite material not only has a damage self-reporting function, but also can realize the repair and recycling of fiber reinforced resin-based composite materials. The epoxy resin system of the present invention has the advantages of low viscosity and easy molding. At the same time, the composite material shows a strong color change (damage self-reporting function) under the action of external force, and this color can be maintained for a long time (about 5 months), providing an effective and accurate prediction capability for material damage caused by mechanical impact. More importantly, the composite material can also repair cracks, gaps and other difficult-to-detect damage many times to meet the performance requirements of continued service. In addition, epoxy resin energy and fiber energy can be completely separated, and the recycled fiber reinforcement is consistent with the original fiber performance structure. The fiber reinforced epoxy resin-based composite material prepared by the present invention effectively saves a large amount of fiber resources and has practical application value under the concept of circular economy.
[0155] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.
Claims
1. A method for preparing a repairable and recyclable fiber-reinforced resin-based composite material with damage reporting, characterized in that: The following steps are involved: The diglycidyl tetrahydrophthalate and polyethyleneimine are uniformly mixed to obtain a pre-gel solution; Adding microcapsules to a pregel solution to obtain a mixed pregel solution; wherein the preparation steps of the microcapsules include: uniformly mixing deionized water, urea, and formaldehyde, adjusting the pH to alkaline with triethylamine, and maintaining the mixture under magnetic stirring at 55° C. for 2 hours to obtain a prepolymer solution; slowly dropping an anionic emulsifier sodium dodecyl sulfate aqueous solution or sodium dodecylbenzene sulfonate aqueous solution into the prepared prepolymer solution for emulsification, wherein the emulsification condition is to treat the mixture at 60° C. for 3 hours, then adding 2,7-dichlorofluorescein, stirring the mixture for 20 minutes, slowly adjusting the pH of the emulsion to 3-4 with phosphoric acid or sulfuric acid, and reacting the mixture for 3 hours to obtain a microcapsule suspension; cooling the obtained microcapsule suspension to room temperature, rinsing the mixture with deionized water and acetone, and drying the mixture to obtain microcapsules within a certain size range; Through the RTM process, the mixed pre-glue liquid is injected into the fiber preform under a pressure of 0.15MPa, cured and cross-linked, and a fiber-reinforced resin-based composite material is obtained; before the mixed pre-glue liquid is injected into the fiber preform, it is first placed in a vacuum oven at 40°C for 30 minutes to remove gas in the resin liquid; the curing conditions are: treatment at 70°C for 3 hours, treatment at 160°C for 3 hours, and treatment at 190°C for 2 hours.
2. The method according to claim 1, characterized in that The fibers in the fiber-reinforced resin-based composite material are long fiber reinforcements, the mass fraction of the long fiber reinforcements accounts for 65-70% of the total content of epoxy resin, curing agent and fiber; the weight fraction of the microcapsules accounts for 1-5% of the total content of epoxy resin and curing agent.
3. A repairable and recyclable fiber-reinforced resin-based composite material with damage reporting prepared according to the method of any one of claims 1 to 2.
4. The fiber-reinforced resin-based composite material according to claim 3, characterized in that: When the fiber-reinforced resin-based composite material is impacted by external force, the core material released from the damaged microcapsules undergoes proton exchange with the amine groups in the resin, causing the damaged area to appear bright yellow, showing mechanochromism, and then self-reporting damage at the damaged location.
5. The fiber-reinforced resin-based composite material according to claim 3, characterized in that: After the fiber-reinforced resin-based composite material is damaged, pressure is applied to the composite material, and the damage heals after a certain period of time.
6. The fiber-reinforced resin-based composite material according to claim 3, characterized in that: The fiber-reinforced resin-based composite material is degraded in an ethylene glycol solution at 160°C.
Citation Information
Patent Citations
A bifunctional epoxy resin composite material and its preparation method
CN113429741B
Microcapsule with damage hinting and repairing functions and application thereof in epoxy coating
CN106118367A
Difunctional epoxy resin composite material and preparation method thereof
CN113429741A